Comparative pathology of lymphoid organs in experimental Newcastle and infectious bursal disease - MANJUNATH, M T; VIJAYASARATHI, S K; SATHYANARAYANA, M L; SREENIVAS GOWDA, R N (The Indian Journal of Animal Sciences, 2014)
Velogenic viscerotropic Newcastle disease (ND) and infectious bursal disease (IBD) were experimentally induced in 4-week-old broilers for comparative study of their impact on lymphoid organs. Evaluation of histological lesions revealed progressive Iymphocytolysis in the thymus, bursa, spleen, caecal tonsils including submucosal lymphoid tissue and Harderian glands in order of severity in ND, whereas, in IBD, lymphocytolysis in the bursa was followed by follicular epithelialization and partial lymphoid repopu!aton by 6 10 7 days post-infection. Alterations in other organs were less severe and transient with lymphoid hypeiplasia in the spleen and caecal tosils.